Freshwater Algal Toxins: Monitoring and Toxicity Profile (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cyanobacterial abundance has increased disproportionately, and this trend is likely to continue in the coming decades. This increase not only has deleterious effects on ecosystem biodiversity but also adversely affects drinking water supplies, livestock watering, crop yields, aquaculture, etc. Thus, the proliferation of cyanobacterial blooms presents human and animal health risks due to the common production of potent toxins, cyanotoxins. Moreover, these risks are aggravated by the accumulation potential of cyanotoxins and their transference to the food chain. In spite of the worldwide increasing occurrence of cyanotoxins, they are still underestimated in regulations. However, risk management of cyanotoxins is only possible after a thorough risk evaluation, and for that purpose, toxicity and exposure data are required. Thus, occurrence and monitoring information is of key importance, and new data in relation to the conditions that favor cyanobacterial growth and cyanotoxin production are welcome in order to prevent their appearance. On the other hand, in regard to toxicity, there are still many data gaps to fill. This book compiles 10 research papers and a review, which provide valuable contributions on all these aspects and demonstrate the importance of cyanobacteria toxins research.